IMPLEMENTATION OF LAW ENFORCEMENT AGAINST HATE SPEECH THROUGH SOCIAL MEDIA IN ELECTION CAMPAIGN ACTIVITIES IN THE JURISDICTION OF THE CENTRAL KALIMANTAN REGIONAL POLICE - Nur Aida Fitriana; Yacob F. Martono; Karlinae D. Bangas; Rizki Setyabowo Sangalang (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
Social media has become a primary tool for election campaigns in Indonesia, but it has also fueled the rise of hate speech practices that have the potential to disrupt democracy and social stability. This study aims to analyze the implementation of law enforcement against hate speech through social media in election campaign activities within the jurisdiction of the Central Kalimantan Regional Police and to identify the obstacles faced by law enforcement officers. The research method used is empirical juridical with a descriptive approach through literature studies and interviews with the Central Kalimantan Regional Police. The results of the study indicate that the implementation of law enforcement against hate speech through social media in election campaign activities within the jurisdiction of the Central Kalimantan Regional Police is carried out through three main approaches: preventive, pre-emptive, and repressive. Preventive efforts are carried out through legal socialization, digital literacy education, and cyber patrols. Pre-emptive efforts are carried out through early detection of potential violations and coordination with Bawaslu, KPU, and Kominfo. Meanwhile, repressive efforts are carried out through investigations, inquiries, and prosecutions based on the law. However, this implementation is less effective and still faces several obstacles. Preventive efforts face challenges such as weak outreach and early monitoring, preemptive efforts face challenges such as a lack of early detection and a structured persuasive approach, and repressive efforts face challenges such as technical digital evidence and inconsistent law enforcement. These challenges indicate that the Central Kalimantan Regional Police (Polda Kalteng) still faces several shortcomings in handling hate speech cases on social media during election campaigns. These challenges stem from unclear and overlapping regulations between election criminal provisions, the Electronic Information and Transactions Law, and technical regulations governing election organizers, leading to differing interpretations among law enforcement agencies. Therefore, it is necessary to strengthen inter-agency coordination and increase the capacity of law enforcement officers to handle hate speech cases during election campaigns so that they can be implemented effectively and fairly.